Teacher Readiness to Face the Learning of Students with Special Needs at SDN 002 Samarinda Kota - Novia Tri Puspita; Sukriadi Sukriadi; Iksam Iksam; Taufik Hidayat; Lily Fitrianie (Journal of Educational Sciences, 2026)
Inclusive education requires teachers to be pedagogically prepared to address the diverse learning needs of children with special needs in regular classrooms. This study aimed to analyze the level of teachers’ readiness in implementing inclusive education at an elementary school. A descriptive embedded mixed-methods design was employed, integrating quantitative questionnaire data and qualitative interview findings to obtain a comprehensive understanding of teacher preparedness. The study involved 28 teachers, with six selected for in-depth interviews using purposive sampling. Quantitative data were analyzed using descriptive statistics, while qualitative data were used to strengthen interpretation of the results. The findings indicate that teachers generally demonstrate positive attitudes toward inclusive education (95%) however, their pedagogical readiness remains moderate, particularly in adaptive lesson planning, differentiated instruction, classroom management, and inclusive assessment. The gap between attitudes and practical competence is associated with limited access to professional development, insufficient specialist support, and structural constraints such as large class sizes and inadequate facilities. These results highlight the importance practice-based teacher training, structured mentoring from competent parties, and institutional support to ensure that inclusive education is implemented effectively, equitably, and sustainably.